Who gets to be an ELT course book author? Native speakerism in English for specific purposes and business English course books - Kiczkowiak, Marek (Frontiers in Education, 2024)
Native speakerism has a profound influence on many aspects of ELT, for example negatively affecting job opportunities of those perceived as 'non-native speakers'. Nevertheless, little is known about the effect of native speakerism on the recruitment of course book authors (CBAs). Therefore, this study analysed the linguistic and ethnic representation of 161 CBAs of 77 business English business English and English for specific purposes English for Specific Purposes course books (CBs) published globally by Pearson, OUP, CUP, Macmillan and NGL.The data clearly show that publishers tend to hire white 'native speakers' from the UK as CBAs. More specifically, 90% of all CBA slots were taken by 'native speakers', 95% by white CBAs, and 78% by CBAs from the UK. This indicates a profound native speakerist bias among publishers against not only 'non-native speakers', but also those 'native speakers' who are not white or do not come from the UK. It is thus suggested that business English and English for Specific Purposes publishers pay greater attention to the diversity of the author teams they hire.